Armazenagem eletroquímica de hidrogênio: um estudo do comportamento dos metais Pd, Nb e V - Bedoch, Audrey Marie (2020)
Developing safe, reliable, efficient and cost-effective methods for hydrogen storage is a scientific and technological challenge. Among possible methods to store hydrogen, storing it in tanks in the liquid or compressed form are not suitable for daily applications due to serious safety problems; unlike solid state storage. Several solid state methods are available, including electrochemical hydrogen storage. The electrochemical hydrogen storage in metals is one of the promising ways to overcome this challenge, because it can be conducted at low temperature and pressure, which brings greater safety and ease of operation. This master's work aimed to implement a pioneering methodology of studies of electrochemical hydrogen storage in the Metal Hydrogen Laboratory (LH2M) at DEMa / UFSCar, through the study of the electrochemical hydrogen storage behavior of pure metals, with different hydrogen absorption characteristics, namely: Pd, Nb and V. The electrochemical properties of the electrodes were measured in an alkaline solution at room temperature, using the potentiodynamic polarization, electrochemical impedance spectroscopy (EIS), galvanostatic charging and potentiostatic discharging techniques. The electrode structures were evaluated before and after the electrochemical charging / discharging tests by X-ray diffraction (XRD). The electrochemical behavior of the pure metals (Pd, Nb and V) and their hydrides are coherent with the thermodynamic prevision, where the equilibrium potential is related to the equilibrium pressure. Through electrochemical hydrogen storage, Pd, Nb and V hydrides formed after galvanostatic charging at -200 mA.cm-2. However, only Pd hydride was reversible, Nb and V hydrides were stable, probably due to the oxide/hydroxide formation on the electrode surface in the alkaline media, which hinders the dehydrogenation reaction.